2007
DOI: 10.2164/jandrol.106.000653
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Concentration, Synthesis, Cell Origin, and Targets in the Rat Caput Epididymis During Sexual Maturation and Variations Associated With Adult Mating Status: Morphological and Biochemical Studies

Abstract: ABSTRACT:The caput epididymis of some mammals contains large quantities of serotonin whose origin, targets, and physiological variations have been poorly studied. We combined morphological and biochemical techniques to begin approaching these aspects of serotonin in the rat caput epididymis. Serotonin immunostaining was detected in mast, epithelial, and neuroendocrine cells. Epithelial cells displayed immunoreactivity to 5HT 1A , 5HT 2A, and 5HT 3 serotonin receptors. Endothelial and mast cells labeled positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
15

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 60 publications
5
58
0
15
Order By: Relevance
“…In rodents, the presence of prominent mast cells in the interstitium of the epididymis is a common background finding that should not be confused with inflammation. The number of mast cells reportedly varies with sexual maturation, reaching a peak at approximately 90 days of age (Jiménez-Trejo et al 2007). …”
Section: Edema (mentioning
confidence: 99%
“…In rodents, the presence of prominent mast cells in the interstitium of the epididymis is a common background finding that should not be confused with inflammation. The number of mast cells reportedly varies with sexual maturation, reaching a peak at approximately 90 days of age (Jiménez-Trejo et al 2007). …”
Section: Edema (mentioning
confidence: 99%
“…We recently found that both 5-HT concentration and TPH activity increase in the epididymis during sexual maturation and in breeding males when compared with naive ones (Jiménez-Trejo et al 2007) and also that epididymal serotonin concentration correlated with reproductive fitness, offspring number, mating success, and seminal plug volume in copulatory males (Pichardo et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Это позволя-ет предположить, что у мужчин с ПЭ может иметь место пони женная чувствительность рецепторов 5-HT2C или гиперсенситивность рецепторов 5-HT1A [12]. На сегод-няшний день доказано существование локальной серо-тонинергической системы в клетках Сертоли, Лейдига и придатке яичка, а также влияние серотонина на стеро-идогенез путем связывания с рецепторами клеток [13][14][15].…”
Section: результатыunclassified